Sex- and Age-Related Differences in Bilirubin Concentrations in Serum Among Population in El-Beida City (Albayan Scientific Journal, 2023)
Bilirubin (BR) is a yellow compound that occurs in the normal catabolic pathway that breaks down heme in vertebrates. The relation between age and sex and the concentration of bilirubin in serum among population in El-Beida City was evaluated in 75 (39%) was female and 118 ( 61%) male . Results from distribution of cases upon age groups in each gender separately (as each group consist of 10 years intervals); Age of the subjects was varied between less than 6 months to more than 75 years. The highest prevalence of the subjects was found in the age group less than six months with 25%. Rest age groups were found almost similar in term of distribution in both genders. Results from distribution of cases upon months in each gender separately; distribution of the subjects was varied between 12 months. The highest prevalence of the subjects was found in the July and August with 40% and 20% respectively. Rest months were found almost similar in term of distribution in both genders. Results found that 60-80% of cases had high level of direct and total bilirubin that significantly differences compared with normal values. .
Keywords: Age; Sex; Bilirubin; El-Baida City; Gender